Comprehensive metabolic analyses provide new insights into primary and secondary metabolites in different tissues of Jianghua Kucha tea (Camellia sinensis var. assamica cv. Jianghua) - Wu, Wenliang; Shi, Jiang; Jin, Jiqiang; Liu, Zhen; Yuan, Yong; Chen, Zhida; Zhang, Shuguang; Dai, Weidong; Lin, Zhi (Frontiers in Nutrition, 2023)
Background Jianghua Kucha (JHKC) is a special tea germplasm with enriched specialized secondary metabolites, including theacrine, non-epimeric flavanols and methylated flavanols. Moreover, primary metabolites provide precursors and energy for the production of secondary metabolites. However, the accumulation patterns of primary and secondary metabolites in different tissues of JHKC are unclear. Methods The changes of primary and secondary metabolites and related metabolic pathways (primary and secondary metabolism) in different JHKC tissues (the bud, 1st-4th leaves, and new stem) were investigated via metabolomics analysis with ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS). Results Significant differences were observed in 68 primary and 51 secondary metabolites mainly related with the pathways of starch and sucrose, amino acids, caffeine, and flavanols metabolism and TCA cycle. The bud exhibited higher levels of glucose-6-phosphate, citric acid, most amino acids, theobromine, catechin-gallate, epicatechin-gallate, procyanidins, and theasinensins; the 1st leaf showed higher levels of caffeine and epigallocatechin-3-gallate; and the 4th leaf contained higher levels of most monosaccharides, theacrine, and epigallocatechin-3-O-(3”-O-methyl)-gallate. In addition, primary metabolites and important secondary metabolites had certain correlations. Conclusion This study provides comprehensive insight into primary and secondary metabolites in JHKC and offers guidelines for efficiently utilizing specialized metabolites of JHKC in the future.